Perbedaan Resiliensi Antara Siswa Yang Aktif Berorganisasi Dengan Siswa Yang Tidak Aktif Berorganisasi di SMA Negeri 1 Pandaan Pasuruan - M. Jadid Khadavi; Estalita Kelly (Ilmu Psikologi Universitas Yudharta Pasuruan)
This research conducted to know whether or not the resilience difference between students who are active joining in organization and who are passive in organization at State Senior High School 1 Pandaan Pasuruan. The sampling technique used quantity sampling for students who are active and simple random sampling for students who are passive. Data collected used resilience scale, seconds data (document), and unstructured interviews to student who are active joining in organization and who are passive in organization. Resilience scale with coefficient of point-biserial correlation between 0,31 to 0,63, and coefficient of reliability by 0,98608779. The data when calculated with inter-groups t-test. This result proof that there are difference between students who are active joining in organization and who are passive in organization, where t-test score by 3,67225 with db 78 is greater than t-tab 1%.